Rapid effects of acute stress on cognitive emotion regulation. (May 2023) - Langer, Katja; Jentsch, Valerie L.; Wolf, Oliver T.
Abstract: Acute stress has been shown to either enhance or impair emotion regulation (ER) performances. Besides sex, strategy use and stimulus intensity, another moderating factor appears to be timing of the ER task relative to stress exposure. Whereas somewhat delayed increases in the stress hormone cortisol have been shown to improve ER performances, rapid sympathetic nervous system (SNS) actions might oppose such effects via cognitive regulatory impairments. Here, we thus investigated rapid effects of acute stress on two ER strategies: reappraisal and distraction. N = 80 healthy participants (40 men & 40 women) were exposed to the Socially Evaluated Cold-Pressor Test or a control condition immediately prior to an ER paradigm which required them to deliberately downregulate emotional responses towards high intensity negative pictures. Subjective ratings and pupil dilation served as ER outcomes measures. Increases in salivary cortisol and cardiovascular activity (index of SNS activation) verified successful induction of acute stress. Unexpectedly, stress reduced subjective emotional arousal when distracting from negative pictures in men indicating regulatory improvements. However, this beneficial effect was particularly pronounced in the second half of the ER paradigm and fully mediated by already rising cortisol levels. In contrast, cardiovascular responses to stress were linked to decreased subjective regulatory performances of reappraisal and distraction in women. However, no detrimental effects of stress on ER occurred at the group level. Yet, our findings provide initial evidence for rapid, opposing effects of the two stress systems on the cognitive control of negative emotions that are critically moderated by sex. Highlights: Stress improved distraction success in men mediated by cortisol increases. Stress indirectly impaired distraction success in women via sympathetic reactivity. No direct stress effects on emotion regulation outcomes in women. Opposing effects of the two stress systems on emotion regulation outcomes.